The Benefits of Gamification on User Experience: A Systematic Literature Review - Putri, Mutia Fadhila; Razi A, Muhammad (CV. Information Technology Training Center - Indonesia (ITTC), 2022)
influence the success of a product, and gamification is one purposed method which is expected to improve the user experience. But actually, whether gamification can provide benefits to increase user experience has not explicitly been explained before. This study purpose identifies the benefits implementation gamification for improving the user experience. To achieve the objectives, this study conducts the systematic literature review that summarized all the studies required in Gamification and User experience context. This study has discovered 539 papers and do three steps to select primary studies through kitchenham method with the results of the first stage is 314 research papers. Then, for the 2nd stage find 50 papers, and finally, the 3rd stage finds 16 best papers. During a systematic literature review, the study is a variety approach depends on two clustered such as intangible and tangible benefits. This study identified gamification have positive intangible and tangible benefits for improving the user experience.